2020
DOI: 10.3389/fmars.2020.589656
|View full text |Cite
|
Sign up to set email alerts
|

Sandy Beach Macrofauna of Yucatán State (Mexico) and Oil Industry Development in the Gulf of Mexico: First Approach for Detecting Environmental Impacts

Abstract: Guerra-Castro et al.Macrofauna and Pollution of Yucatán Beaches than those considered as lower-threshold values for marine sediments. The biological and chemical patterns reported here indicated that it is an appropriate moment to start long-term monitoring. The sampling design we suggest is based on statistical precision and internationally recognized protocols for assessment of marine diversity on sandy beaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 95 publications
0
3
0
Order By: Relevance
“…Tourist impacts can be so damaging that Niefer (2002) suggests continuous monitoring of visitors, the establishment of information centers, educational trails, and environmental education projects. Recently, Guerra-Castro et al (2020) used an open beach biodiversity assessment methodology to establish solid baselines to compare in cases of extreme impacts applied in Mexican tourist and non-tourist beaches.…”
Section: Introductionmentioning
confidence: 99%
“…Tourist impacts can be so damaging that Niefer (2002) suggests continuous monitoring of visitors, the establishment of information centers, educational trails, and environmental education projects. Recently, Guerra-Castro et al (2020) used an open beach biodiversity assessment methodology to establish solid baselines to compare in cases of extreme impacts applied in Mexican tourist and non-tourist beaches.…”
Section: Introductionmentioning
confidence: 99%
“…In any case, the large disparity in the diversity between the two studies, together with the revealed deficit in the detection of species in this study, as seen in the species accumulation curves, reinforces the idea that, despite the great sampling effort, the Río Lagartos coastal lagoon has greater mollusc diversity, and likely spatio-temporal heterogeneity, than reported in this or previous studies. This highlights the lack of information from the region that will be necessary to achieve solid ecological baseline knowledge (Guerra-Castro et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Recognizing the importance of these services, numerous international collaborations (Benson et al, 2018;Canonico et al, 2019) have centered their efforts to enhance monitoring, setting essential physical, chemical, and marine biological variables to be measured through standardized methods and best practices of data acquisition to subsidize conservation, management, and stackeholders decisions (Pereira et al, 2013;Miloslavich et al, 2018;Fanini et al, 2020;Guerra-Castro et al, 2020). In this sense, sandy beaches are key monitoring sites.…”
Section: Introductionmentioning
confidence: 99%